Suspending the next turn as a form of repair initiation: evidence from Argentine Sign Language - Manrique, Elizabeth; Enfield, N. J. (Frontiers in Psychology, 2015)
Practices of other-initiated repair deal with problems of hearing or understanding what another person has said in the fast-moving turn-by-turn flow of conversation. As such, other-initiated repair plays a fundamental role in the maintenance of intersubjectivity in social interaction. This study finds and analyses a special type of other-initiated repair that is used in turn-by-turn conversation in a sign language: Argentine Sign Language (Lengua de Señas Argentina or LSA). We describe a type of response termed a ‘freeze-look’, which occurs when a person has just been asked a direct question: instead of answering the question in the next turn position, the person holds still while looking directly at the questioner. In these cases it is clear that the person is aware of having just been addressed and is not otherwise accounting for their delay in responding (e.g., by displaying a ‘thinking’ face or hesitation, etc.). We find that this behavior functions as a way for an addressee to initiate repair by the person who asked the question. The ‘freeze-look’ results in the questioner ‘re-doing’ their action of asking a question, for example by repeating or rephrasing it. Thus we argue that the ‘freeze-look’ is a practice for other-initiation of repair. In addition, we argue that it is an ‘off-record’ practice, thus contrasting with known on-record practices such as saying ‘Huh?’ or equivalents. The findings aim to contribute to research on human understanding in everyday turn-by-turn conversation by looking at an understudied sign language, with possible implications for our understanding of visual bodily communication in spoken languages as well.